DECOMPOSITION OF EXHAUST EMISSIONS FROM THE PORTABLE INCINERATOR - Sudrajad, Agung (Department of Mechanical Engineering, Universitas Sultan Ageng Tirtayasa, 2023)
Combustion is a chemical process called exothermic reaction, where all chemical reaction involves energy to break bonds in reactants, and energy is released when new bonds form in products. The combustion process that occurs in the incinerator is an exothermic reaction where hydrocarbon reacts with oxygen to produce heat, carbon dioxide (CO2), and water vapor. However, in general combustion process that occurs is usually an imperfect reaction that creates harmful gas emissions. In this research, the author uses an electrostatic precipitator to filter emissions produced by the incinerator. An incinerator is a furnace used to treat solid waste, then turn it into gas, and ashes (fly ash and bottom ash). The experiment compares the combustion emission with the usage of ESP and without ESP. The experiment used a portable gas analyzer to gather emission data. The result of this research shows that ESP can reduce emissions from incinerator by 41% in filtering carbon monoxide (CO),18% in filtering hydrocarbon (HC), and 11% in filtering carbon dioxide (CO2). The oxygen value increases by 8% in ESP turned-on condition.